Penentuan Kandungan Metabolit Sekunder, Fenolik Total serta Uji Aktivitas Antibakteri dan Antijamur Ekstrak Daun Sungkai (Peronema canescens Jack) di Kabupaten Agam dan Kota Padang - -, Norman Ferdinal; Ningsih, Yanisa Fitria; Afrizal, Afrizal (Departemen Kimia Universitas Andalas, 2024)
Sungkai (Peronema canescens Jack) is the traditional medicinal plants used in Indonesia. The purpose of this study was to determine the content of secondary metabolites, total phenolic content and test the antibacterial and antifungal activity of Sungkai plant leaf extract. Extraction was carried out by gradual maceration using 3 solvents with different polarity, starting from hexane, ethyl acetate and methanol. The results showed that the phytochemical profile of Sungkai leaves contained flavonoids, phenolics, saponins, triterpenoids, steroids and alkaloids. In the total phenolic test using the Folin-Ciocalteau method. The highest total phenolic content was found in the methanol extract of 195.8 mgGAE/g sample for the Padang City. The antibacterial and antifungal activity of Sungkai leaf extract were tested using the Well diffusion method. The largest diameter of the clear zone on antibacterial activity was produced in the ethyl acetate extract of the Kab. Agam with a concentration of 50% is 7 mm in Escherichia coli bacteria and 5.6 mm in Staphylococcus aureus bacteria. The highest antifungal activity against Candida albicans was produced in the ethyl acetate extract of the Padang City area of ​​6.4 mm. The ability of the extract activity is still much lower when compared to the positive control